Physiological and perceptual responses to three consecutive official matches in female boxer. A case study - Obmiński Zbigniew; Turowski Dariusz (Sciendo, 2014)
Study aim: The purpose of this study was to assess the physiological cost of three consecutive official boxing fights played during a 3-day tournament and two non-contact specific drills against handheld pads of the same time-profile as the contest, 4 × 2 minutes with 1-minute intervals between them. This assessment was based on the determination of selected hormones and metabolites in the blood sampled directly prior to the contests and throughout short-term post-contest recovery.